Can you saolve this please? thanks! #y''-2y'+y=e^x/sqrt(4-x^2)#

Answer 1

#y = e^(x)( x sin^(-1) (x/2) + sqrt(4-x^2) + alpha x + beta )#

#y''-2y'+y=e^x/sqrt(4-x^2)#

This is:

#(D-1)^2 y =e^x/sqrt(4-x^2)#, with operator #D = d/(dx)#
Let #z = (D-1) y#:
#(D-1) z =e^x/sqrt(4-x^2)#

Or:

#z'- z =e^x/sqrt(4-x^2)#
Integrating factor: #mu(x) = e^(- int\ dx ) = Ae^(-x)#
#mu( z'- z =e^x/sqrt(4-x^2))#
#implies (z e^(-x))^' =1/sqrt(4-x^2)#
#z e^(-x) = int \ dx \ 1/sqrt(4-x^2) qquad square#
With #x = 2 sin A#, the RHS is:
# = int \ dA \ (2 cos A )/(2cos A) = A + " const" = sin^(-1) (x/2) + " const" #
#square# becomes:
#z = (D-1) y = e^x sin^(-1) (x/2) + alpha e^x #

This is:

#y' - y = e^x sin^(-1) (x/2) + alpha e^x#
With the same Integrating factor: #mu(x) = e^(- int\ dx ) = Ae^(-x)#
#mu(y' - y = e^x sin^(-1) (x/2) + alpha e^x)#
#implies y e^(-x) = int dx qquad sin^(-1) (x/2) + alpha qquad circ #
Second part is trivial of RHS, and first part can be IBP'd using the result that follows #square#.
# int dx \ (x)^' sin^(-1) (x/2)#
# x sin^(-1) (x/2) - int dx \ x (sin^(-1) (x/2))^'#

From the preceding integration:

# = x sin^(-1) (x/2) - int dx \ x/sqrt(4-x^2)#

Pattern matching:

# = x sin^(-1) (x/2) - int dx \ (-sqrt(4-x^2) )^'#
# = x sin^(-1) (x/2) + sqrt(4-x^2) + beta #
#circ# now reads:
#y e^(-x) =x sin^(-1) (x/2) + sqrt(4-x^2) + alpha x + beta#
#implies y = e^(x)( x sin^(-1) (x/2) + sqrt(4-x^2) + alpha x + beta )#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To solve the given differential equation ( y'' - 2y' + y = \frac{e^x}{\sqrt{4 - x^2}} ), we first solve the associated homogeneous equation ( y'' - 2y' + y = 0 ), which has characteristic equation ( r^2 - 2r + 1 = 0 ).

The characteristic equation has a repeated root ( r = 1 ), so the solution to the homogeneous equation is ( y_h(x) = (C_1 + C_2x)e^x ), where ( C_1 ) and ( C_2 ) are constants.

Now, we look for a particular solution to the non-homogeneous equation. We use the method of undetermined coefficients.

Given that the right-hand side is ( \frac{e^x}{\sqrt{4 - x^2}} ), we assume a particular solution of the form ( y_p(x) = Ae^x ), where ( A ) is a constant to be determined.

Taking derivatives and substituting into the original differential equation, we find ( A = \frac{1}{2} ).

Therefore, the particular solution is ( y_p(x) = \frac{1}{2}e^x ).

The general solution to the non-homogeneous equation is the sum of the homogeneous and particular solutions:

[ y(x) = y_h(x) + y_p(x) = (C_1 + C_2x)e^x + \frac{1}{2}e^x ]

where ( C_1 ) and ( C_2 ) are constants determined by initial conditions, if provided.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7